PREPARING EVALUATION OF TOLL CONSTRUCTION PROJECT PLANS USING CRITICAL PATH METHOD (CPM) FOR TRANS SUMATERA TOLL SECTION - Yusuf Luqman; Meilita Tryana Sembiring; Iskandarini (RADJA PUBLIKA, 2023)
The rapid development of technology drives competition and efficiency in Information Technology projects. Toll road projects in Indonesia, such as the Trans Sumatra Toll Road and inner-city toll roads in Jakarta, face challenges of delays. The Critical Path Method (CPM) is used to plan and evaluate these projects for improved efficiency. Evaluation of project plans is necessary to complete pending tasks. This descriptive research utilizes Job and Activity Analysis to collect quantitative data on time, cost, and resources from construction activities on the Sumatra Toll Road. The collected data is then processed using CPM to create a schedule, identify critical paths, and evaluate float times. The research provides efficient project scheduling recommendations to complete the remaining tasks on the Sumatra Toll Road project. The study concludes that by adhering to the schedule, the project can be completed on time. Delays in previous projects were primarily caused by land acquisition issues. To prevent further schedule delays, preventive strategies and resource augmentation should be considered. In summary, this research contributes efficient project scheduling recommendations to complete the remaining tasks on the Sumatra Toll Road project.